Peran Spiritualitas dalam Meningkatkan Resiliensi pada Residen Narkoba - Diky Permana (Syifa al-Qulub, 2018)
This article was written based on research on the Role of Spirituality in Increasing Resilience in Resident Drugs at Pondok Pesantren Inabah XX Tasikmalaya. This study used qualitative descriptive method. The approach is psychological-spiritual. The point of the argument from this study, to know the extent to which the role of spirituality can affect the level of resilience in drug residents in following the spiritual-based rehabilitation. From this study it was found that drug residents were able to increase resilience when attending spiritual-based rehabilitation.